On a Scientific Approach for Deep Time Investigations - T. Mark Harrison (Perspectives of Earth and Space Scientists)
Abstract I came to geology through a metaphoric back door and was gifted a series of visionary mentors who imbued me with an outside‐the‐box view of Earth history. Coupled with remarkable advances in microscale analytical capabilities that arose just as I was graduating into the field, that unorthodox view permitted my research group to explore an alternate conception of the longstanding paradigm of earliest Earth history. As I look back on how the field has evolved in my 40 year career, I see a mixed record of significant advances in our understanding alongside a persistent groupthink that discourages creativity and individual responsibility. I've come to understand this as reflecting different intellectual requirements of deep time geology relative to the study of modern processes. This difference between the general understanding of the scientific method and our needs has given cover to an unconstructive habit. My field is ripe for a fundamental change in the way we address the meager and almost certainly biased geologic record. This disruption could lead younger scientists and future generations away from poorly justified consensus models toward a more complete understanding of the darkest age of our planet's history.